Improved stability conditions of time-varying delay systems based on new Lyapunov functionals - Lee, Tae H.; Park, Ju H. (Journal of the Franklin Institute, 2018)
This paper is concerned with the stability analysis of time-varying delay systems. Unlike the construction of augmented Lyapunov functional and multiple integral Lyapunov functional, novel three Lyapunov functionals are suggested which are delay product type functions and lead to less conservative results. Based on newly developed Lyapunov functionals, three stability criteria are derived and their superiority is described by three numerical examples.